Popular Lived Culture in Communist Romania (1945–1989) as Retraced in Life Histories: How People Appropriated or Resisted Products, Practices, Trends, and Elements of Lifestyle - Simona Rodat (Univerzita Karlova, Filozofická fakulta, 2020)
Due to its character of totalitarian regime and through the major changes imposed in the society, the communist regime in Romania between 1945 and 1989 represents a distinct period in the history of the country. A series of inflicted macrosocial processes, such as the strictly centralized economy, collectivization and nationalization, as well as some phenomena such as the control of citizens’ lives, the impossibility of free expression, censorship of the press and culture, the lack of consumer goods, restrictions on utilities, and so on, negatively marked the fate of many Romanians during this period. However, many people remember this period with nostalgia. The present paper deals with the popular culture in Romania during the communist period (1945–1989), as seen, considered, and remembered by people who lived in that era, or at least in a period of it. The research was based on the method of life histories and focussed on the viewings of the subjects regarding the practices, rituals, artefacts, and products of popular culture in the communist time. Both folk culture and mass culture are discussed and analysed, as well as the elements of lifestyle, as described by the subjects. Moreover, the influences on the popular culture in that period are outlined, such as those of some large-scale phenomena like industrialisation and urbanisation, Western trends, Soviet propaganda, or the different impositions of the Romanian authorities, according to the various stages the communist regime has been going through in this period. The gathered data show that, while many memories of people are sorrowful and bitter, other recalls and considerations regarding the cultural practices of that time, and especially the human relations built by the means of these practices, are full of nostalgia. These aspects concerning popular culture in a particular historical period and nostalgia related to it are discussed in detail in the paper.